Natural team sharing and team productivity - Fabella, Raul V.
We show that when effort levels are observable, natural team sharing where one's proportional share in total output equals one's proportional share in total input, sustains a first-best production level only for a function unique up to a constant of proportionality.
A copy is also available at the UPSE Library Archives (Faculty Publications).
Keywords: Work sharing; Teams in the workplace